Limiting GPR in a two-layer soil model via genetic algorithms - Gursu, Baris; Ince, Melih Cevdet (Pergamon-Elsevier Science Ltd, 2009)
In this paper, an optimum grounding grid that provides the conditions of GPR
Keywords: Ground potential rise (GPR); Maximum allowable touch voltage (E-touch); Two-layer soil model; Genetic algorithms; Optimum grounding grid design